Factors Predicting Increased Length of Stay in Abdominal Wall Reconstruction. Issue 5 (May 2023) - Elhage, Sharbel A.; Ayuso, Sullivan A.; Deerenberg, Eva B.; Shao, Jenny M.; Prasad, Tanushree; Kercher, Kent W.; Colavita, Paul D.; Augenstein, Vedra A.; Todd Heniford, B.
Background: Enhanced recovery after surgery (ERAS) programs have become increasingly popular in general surgery, yet no guidelines exist for an abdominal wall reconstruction (AWR)–specific program. We aimed to evaluate predictors of increased length of stay (LOS) in the AWR population to aid in creating an AWR-specific ERAS protocol. Methods: A prospective, single institution hernia center database was queried for all patients undergoing open AWR (1999-2019). Standard statistical methods and linear and logistic regression were used to evaluate for predictors of increased LOS. Groups were compared based on LOS below or above the median LOS of 6 days (IQR = 4-8). Results: Inclusion criteria were met by 2, 505 patients. On average, the high LOS group was older, with higher rates of CAD, COPD, diabetes, obesity, and pre-operative narcotic use (all P < .05). Longer LOS patients had more complex hernias with larger defects, higher rates of mesh infection/fistula, and more often required a component separation (all P < .05). Multivariate analysis identified age (β0.04, SE0.02), BMI (β0.06, SE0.03), hernia defect size (β0.003, SE0.001), active mesh infection or mesh fistula (β1.8, SE0.72), operative time (β0.02, SE0.002), and ASA score >4 (β3.6, SE1.7) as independently associated factors for increased LOS (all P < .05). Logistic regression showed that an increased length of stay trended toward an increased risk of hernia recurrence ( P = .06). Conclusions: Multiple patient and hernia characteristics are shown to significantly affect LOS, which, in turn, increases the odds of AWR failure. Weight loss, peri-operative geriatric optimization, prehabilitation of comorbidities, and operating room efficiency can enhance recovery and shorten LOS following AWR.